The Influence of Artificial Intelligence on Data System Security - Hasan, Syed Nazmul; Kaur, Harleen; Mohonta, Sraboni Clara; Siddiqa, Kazi Bushra; Kaur, Jobanpreet; Haldar, Urmi; Chy, Аsikur Rаhmаn; Manik , Mia Md Tofayel Gonee (International Journal of Computational and Experimental Science and Engineering, 2025)
Data system security has emerged as a top concern for businesses throughout the globe in today's fast-paced digital environment. The increasing sophistication and frequency of cyber-attacks necessitate more sophisticated and flexible forms of defense measures to deal with them. Machine learning, deep learning, and behavioral analytics are all forms of Artificial Intelligence (AI), which has become a revolutionary area of cybersecurity. This paper looks at how AI can enhance the security of a data system in general, and how it can be applied in threat detection, intrusion prevention, malware analysis, and predictive security, in particular. The intertwining of AI technology allows automated responses to potential threats, real-time anomaly detection, and enormous amounts of data processing. This paper gives an informative review of the extent to which AI is transforming the cybersecurity space and enhancing cyber infrastructures through investigating the latest progress and deployment plans.